Gaya Kepemimpinan Koordinator UKP dan Motivasi Kerja Karyawan Puskesmas Sukomoro, Magetan Leadership Style of UKP Coordinator and Employee Motivation of Sukomoro Community Health Center, Magetan - Widiarini, Retno (STIKes Maharani Malang, 2017)
The existence of competing demands from other health practitioners, both public and private status, would to force the primary health centers to think business-like and innovate on the services provided. Sukomoro Public Health CenterÂ as one of the public health centers that would change the status into BLUDs expected to increase their responsibilities in serving health care. It was necessary for the performance of a good employee, the employee must have a highly motivated and loyal to the institution so that the objective the institution would be more easily achieved. It needed to be supported by leadership style, especially coordinators employees who deal directly with the performance of his subordinates and could increase employee productivity and improve service quality. The objective of this study was to analyze the association between UKP coordinator leadership style with employee motivation PHC Sukomoro Magetan. This study used cross sectional design. The study population were all employees UKP include General Poli, health of both mother and child or family planning. The number of samples were 35 people using simple random sampling. Most types of UKP coordinator leadership style was participative leadership style of 65.71%. The level of employee motivation was 51.43% have a high motivation to work. Based on the results of Chi Square test, there was an association between UKP coordinator leadership style with employee motivation Sukomoro PHC Magetan (p=0,024). The results of the test output contingency coefficient of 0.024, which means the level of associationbetween UKP coordinator leadership style with the employee motivation Sukomoro PHCÂ was very low.